2007
DOI: 10.1159/000107425
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Secretion of CXCL8 (IL-8), Release of Tryptase and Transcription of Histidine Decarboxylase mRNA by Anti-IgE-Activated Human Umbilical Cord Blood-Derived Cultured Mast Cells

Abstract: Activation of cytokine receptors and alterations in cytokines are thought to play important roles in neuronal dysfunction and in the pathogenesis of the nervous system diseases. CXCL8 (IL-8) is a CXC chemokine with chemotactic and inflammatory properties. Chemokines control mast cell infiltration in several inflammatory diseases, including stress and neurological dysfunctions. Using isolated human umbilical cord blood-derived cultured mast cells (HUCMC) from hematopoietic stem cells CD34+, mast cells were immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
3
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
(40 reference statements)
1
3
0
Order By: Relevance
“…In support of our observations with BMMC, Castellani et al [39,40] have recently reported that human umbilical cord blood-derived mast cells have increased levels of HDC transcript following IgE receptor cross-linking. One advantage of producing more histamine following activation may be to prepare for subsequent rounds of activation.…”
Section: Discussionsupporting
confidence: 91%
“…In support of our observations with BMMC, Castellani et al [39,40] have recently reported that human umbilical cord blood-derived mast cells have increased levels of HDC transcript following IgE receptor cross-linking. One advantage of producing more histamine following activation may be to prepare for subsequent rounds of activation.…”
Section: Discussionsupporting
confidence: 91%
“…This death process results in the release of inflammatory mediators that serve a variety of roles, including mast cell and leukocyte recruitment. Chemokines such as IL-8 (CXCL8) attract neutrophils and eosinophils to inflammation sites (16). IL-8, in particular, is a proinflammatory cytokine that, when expressed in the airway epithelium, serves as an indicator of cellular inflammation (17).…”
mentioning
confidence: 99%
“…Hemokines control mast cell infiltration in several inflammatory diseases, including stress and neurological dysfunctions (26)(27)(28).…”
mentioning
confidence: 99%
“…CXCL8 (IL-8) is a CXC chemokine with chemotactic and inflammatory properties. We recently found that SP is able to stimulate the release of IL-8 (CXCL8) in mast cells (26,(60)(61). Since CXCL8 is a member of the CXC chemokine subfamily with potent chemotactic activity on neutrophils (62), and is a primary inflammatory cytokine, we conclude that these observations, obtained from human derived cord blood mast cell cultures (HOCBMC), a good and valid model in vitro, support the concept that the neurogenic system modulates inflammatory events by substance P and chemokine CXCL8 release (26,(63)(64).…”
mentioning
confidence: 99%